Risk factors of cartilage lesion after anterior cruciate ligament reconstruction - Huang, Zirong; Cui, Jiaming; Zhong, Mingjin; Deng, Zhenhan; Chen, Kang; Zhu, Weimin (Frontiers in Cell and Developmental Biology, 2022)
Anterior cruciate ligament injury is the most common sports injury in orthopaedics, which can adversely affect knee joint function and exercise of patients. Using arthroscopy to reconstruct the anterior cruciate ligament has become the first choice for treating anterior cruciate ligament rupture. However, different degrees of articular cartilage injury of the knee can be observed in patients after anterior cruciate ligament reconstruction. More importantly, the articular cartilage injury after anterior cruciate ligament reconstruction indicates that it will develop into osteoarthritis in the long term. It is of great significance to fully understand the factors that lead to the occurrence and development of cartilage injury. This article reviews the effects of surgical methods, meniscus status, different grafts, time from injury to surgical intervention, postoperative knee joint stability, postoperative rehabilitation, knee joint anatomical factors, and demographic characteristics of patients on articular cartilage degeneration after anterior cruciate ligament reconstruction. The present review provides insights into the anterior cruciate ligament reconstruction, which can be used to investigate new treatment strategies to delay and prevent the progress of osteoarthritis. At the same time, it provides a holistic understanding of the influence of multiple factors on cartilage lesions after anterior cruciate ligament reconstruction.